Interface-induced plasmon nonhomogeneity in nanostructured metal-dielectric planar metamateria - Kovalev, Anatoly I.; Wainstein, D. L.; Rashkovskiy, A. Y.; Gago, R.; Soldera, F.; Endrino, José L.; Fox-Rabinovich, German S. (Hindawi Publishing Corporation, 2015)
Transformations of the electronic structure in thin silver layers in metal-dielectric (TiAlN/Ag) multilayer nanocomposite were investigated by a set of electron spectroscopy techniques. Localization of the electronic states in the valence band and reduction of electron concentration in the conduction band was observed. This led to decreasing metallic properties of silver in the thin films. A critical layer thickness of 23.5 nm associated with the development of quantum effects was determined by X-ray photoelectron spectroscopy. Scanning Auger electron microscopy of characteristic energy losses provided images of plasmon localization in the Ag layers. The nonuniformity of plasmon intensities distribution near the metal-nitride interfaces was assessed experimentally.